Psycho-social correlates of opioid use disorder among the US adult population: Evidence from the National Survey on drug use and health, 2015-2018 - Haider, Mohammad Rifat; Brown, Monique J; Gupta, Rajat Das; Karim, Sabrina; Olatosi, Bankole; Li, Xiaoming (Taylor & Francis, 2022)
This article was published in Substance Use and Misuse by Taylor & Francis [ Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/10826084.2020.1788086 The Journal's website is at: https://www.tandfonline.com/doi/full/10.1080/10826084.2020.1788086